2021
DOI: 10.1101/2021.07.30.454364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pace of Modern Life, Revisited

Abstract: Wild populations must continuously adapt to environmental changes or they risk extinction. Such adaptations can be measured as phenotypic rates of change and can allow us to predict patterns of contemporary evolutionary change. About two decades ago, a dataset of phenotypic rates of change in wild populations was compiled. Since then, researchers have used (and expanded) this dataset to look at microevolutionary processes in relation to specific types of human disturbances. Here, we have updated the dataset ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…This result contrasts with findings from two recent metaanalyses reporting urban-associated increased phenotypic variation in a variety of life history and morphological traits populations (Capilla-Lasheras et al, 2022;Thompson et al, 2022) but is consistent with large-scale studies demonstrating a lack of clear patterns. Specifically, in a large-scale analysis of phenotypic variation spanning 4507 effect sizes, 196 studies, and 177 species, Sanderson and colleagues found that phenotypic variation did not differ in a generalizable way by either trait type or human disturbance (Sanderson et al, 2023). Despite the absence of general patterns, it is still valuable to explore how phenotypic variation responds to urbanization within specific cases (e.g., species, phenotype, urban characteristic) to better understand the evo-ecological dynamics underlying urban-associated phenotypic change.…”
Section: No Evidence For Differences In Behavioral Variationmentioning
confidence: 99%
“…This result contrasts with findings from two recent metaanalyses reporting urban-associated increased phenotypic variation in a variety of life history and morphological traits populations (Capilla-Lasheras et al, 2022;Thompson et al, 2022) but is consistent with large-scale studies demonstrating a lack of clear patterns. Specifically, in a large-scale analysis of phenotypic variation spanning 4507 effect sizes, 196 studies, and 177 species, Sanderson and colleagues found that phenotypic variation did not differ in a generalizable way by either trait type or human disturbance (Sanderson et al, 2023). Despite the absence of general patterns, it is still valuable to explore how phenotypic variation responds to urbanization within specific cases (e.g., species, phenotype, urban characteristic) to better understand the evo-ecological dynamics underlying urban-associated phenotypic change.…”
Section: No Evidence For Differences In Behavioral Variationmentioning
confidence: 99%